Effect of Pharmaconutrition-Supplemented Parenteral Nutrition for Severe Acute Pancreatitis：A Meta-analysis of Randomized Controlled Trials - Shen, Yinfeng; Deng, Xiaochuan; Jin, Wenyin; Zhang, Chenwei; Zhang, Xingwen; Wang, Ying (JOP. Journal of the Pancreas, 2014)
Objective To evaluate the effectiveness of pharmaconutrition-supplemented parenteral nutrition (PN) for severe acute pancreatitis (SAP). Methods A comprehensive search of abstracts was performed in the MEDLINE, OVID, Springer, and Cochrane Library database. Published data of randomized clinical trials (RCTs) comparing the clinically relevant outcomes of pharmaconutrition-supplemented PN versus PN for patients with SAP were analyzed. The analyzed outcome variables included infection, mortality, intensive care unit (ICU) stay, hospital stay, and leukocytes change. Statistical analyses were performed using the Cochrane Collaboration’s RevMan 5.1 software. Results Four RCTs published in 1998 or later were included in this meta-analysis, in which 76 patients with pharmaconutrition-supplemented PN and 77 patients with PN. Pharmaconutrition-supplemented PN showed significantly better results in terms of infection (OR, 0.42; 95% CI, 0.20–0.91; P =0.03) and leukocytes change (before treated: mean different, 0.93; 95% CI, 0.21–1.65; P =0.01; after treated: mean different, -0.77; 95% CI, -1.47– -0.08; P =0.03). No significant difference could be found in mortality (OR, 0.30; 95% CI, 0.07–1.19; P =0.09), ICU stay (mean different, -3.65; 95% CI, -9.39–2.10; P =0.21), and hospital stay (mean different, -1.20; 95% CI, -9.89–7.48; P =0.79). Conclusions The current meta-analysis indicates that pharmaconutrition-supplemented PN only show advantages in infection and leukocytes change. Image: Forest plot for infection.